Is abdominal x-ray (AXR) or computed tomography (CT) of the abdomen the most appropriate imaging modality for the detection of illegal substances concealed, taking into consideration the sensitivity, specificity and radiation dose?. (March 2019) - Lan, Kiki; Doyle, Edel
Highlights: CT is superior to AXR in terms of sensitivity and specificity. Low-dose CT abdomen is most appropriate for investigating suspected body packers. DECT research to characterise drug packets in symptomatic suspects is recommended. Abstract: Body packing is the internal concealment of illicit substances within the alimentary tract with the intention of smuggling them across borders and evading law enforcement. Medical imaging plays an important role in the management of suspected body packers through the identification of drug packets, as well as recognising medical complications. This literature review aims to determine whether abdominal radiography (AXR) or computed tomography [CT] is the most appropriate imaging modality for the detection of illegal substances in suspected body packers, taking into consideration the sensitivity, specificity and radiation dose. In addition, whether CT could completely replace the use of radiography given the radiation dose of CT can be decreased to levels that can be comparable to x-ray. AXR is a widely available and relatively low-dose modality commonly performed as the first line of imaging for suspected body packers but is very unreliable due to its highly variable sensitivity of 40–90% and high false positive and false negative rates. CT has a reported sensitivity and specificity of close to 100% but is not used as an initial imaging modality due to its higher radiation dose. CT is not only superior in sensitivity and specificity, but radiologists are also able to accurately identify the number of packets and their locations within the body while delivering radiation doses similar or even below the average dose of an AXR. The use of a low-dose CT protocol with reduced mAs is now preferred as the initial screening tool for suspected body packers over AXR.